The Influence of the Role of Parents, Teachers, and Curriculum on Students' Cognitive Skills with the Moderating Role of Socioeconomic Factors - Rinovian Rais; Sungguh Ponten Pranata; Djuwairiyah (Universitas Pendidikan Ganesha, 2025)
The development of students' cognitive skills is influenced by various factors, but socioeconomic disparities often create obstacles to equitable learning outcomes. This study aims to investigate the effects of parental involvement, teacher quality, and curriculum implementation on students' cognitive skills, considering the moderating role of socioeconomic factors. Using a quantitative approach, data were collected from students, parents, and teachers in several schools. The study subjects consisted of 200 students selected through purposive sampling. Data were collected through a structured questionnaire distributed to the selected students. The obtained data were then analyzed through path analysis conducted using Smart PLS 4.0. The results indicate that all three factors have a positive and significant effect on students' cognitive skills, with parental involvement being the most dominant factor. Although socioeconomic factors moderate this relationship, the impact is less significant than expected. These findings emphasize the importance of improving teacher quality, encouraging parental participation, and designing adaptive curricula to support the cognitive development of all students, regardless of socioeconomic background.